Histopathological findings in obese patients undergoing laparoscopic sleeve gastrectomy in the Western region of Saudi Arabia - Samah Saharti; Reem Aljohani (Annals of Saudi Medicine)
BACKGROUND: Metabolic and bariatric surgeries are effective interventions in reducing weight and mortality. Laparoscopic sleeve gastrectomy is the most commonly performed procedure, particularly in the Middle East and North Africa (MENA) region. It involves resection of approximately 80% of the stomach, yielding large specimens for histopathological evaluation. OBJECTIVES: To identify histopathological findings in gastric specimens, evaluate the incidence of unexpected gastrointestinal stromal tumors (GISTs), and characterize the metabolic and bariatric surgery population in Saudi Arabia. DESIGN: Retrospective cohort SETTINGS: Single-center tertiary care in Saudi Arabia PATIENTS AND METHODS: The study included patients who underwent laparoscopic gastric sleeve between May 2015 and April 2021. Inclusion criteria were patients with BMI ≥ 30 kg/m2 who underwent surgery as treatment for obesity. MAIN OUTCOME MEASURES: Gastric histopathological findings, unexpected GIST incidence and metabolic and bariatric surgery population. SAMPLE SIZE: 211 patients with obesity RESULTS: Patients' mean age was 38.2 years with a mean Body mass index (BMI) of 44.24 kg/m2. The majority were females (60.2%). Normal histology findings accounted for 43.1% of findings, followed by chronic inactive gastritis (35.5%). Intestinal metaplasia was found in 1 (0.5%) patient while incidental GIST was found in 2 (0.9%) patients. Helicobacter pylori (H. pylori) was identified in 12.8% of cases, with a mean patient age of 36.7 years. Among H. pylori-positive patients, 48% presented with chronic active gastritis, 33% with chronic inactive gastritis, 14.8% with active follicular gastritis, and 3.7% with inactive follicular gastritis. A history of prior endoscopy was noted in 16.1% of patients, of whom 11.76% were found to have H. pylori postoperatively. CONCLUSIONS: H. pylori infection was detected at a mean age of 36.7 years and showed a significant association with higher BMI (mean difference: 2.2 kg/m2, P=.04). While this suggests a potential link between obesity and H. pylori susceptibility, the clinical significance of this small absolute difference requires further investigation. H. pylori remained strongly associated with follicular gastritis (P=.003) but showed no difference between males and females. LIMITATIONS: Retrospective design and Giemsa stain was not done for all specimens to investigate H. pylori.